The impact of different size herbivores on plant biomass in Yamal (Russia) - Baubin, Capucine (UiT Norges arktiske universitet, 2016)
Tundra ecosystems are changing environments that are greatly affected by plant-herbivore relationships. Many herbivores of different sizes eat, trample or clip plants. However they can also act as support through nutrient addition by faeces. In this study I look at the impact of three sizes of herbivores (large, medium and small) on ten functional groups of plants (nitrogen-fixing forbs, erect willows, birch bushes, evergreen ericoids, nitrogen-non-fixing forbs, grasses, sedges, deciduous shrubs, semi-evergreen shrubs and toxic plants) in three habitats of differing productivity and importance for herbivores on the Yamal Peninsula in Russia. My research question is: “is the impact of herbivores cumulative on palatable plants and complementary on less palatable plants?”. To answer this question, I investigated the first year data from an exclosure experiment that was set up in 2014. There were tendencies suggesting that herbivores do not always have a cumulative impact on palatable plants and that the impact on less palatable plants is not always complementary. However, based on plant traits, herbivores’ preferences and previous studies I conclude that the fastest growing plants usually show responses already after a very short time of herbivore exclusion. Further research during the next years will shed light on persistence of these results.